A Role for the Right Anterior Temporal Lobe in Taste Quality Recognition - Small, Dana M. (J Neurosci, 1997)
We conducted two experiments to examine central processing of the taste of citric acid. In the first experiment, elevated citric acid recognition thresholds, but normal detection thresholds, were observed in a group of patients who had undergone a rightanterior temporal lobectomy for the treatment of epilepsy, compared with a control group and a group of patients who had undergone the same operation in the left hemisphere. In the second study, using positron emission tomography, we compared regional cerebral blood flow (rCBF) in a condition in which citric acid was presented with one in which water was presented (with similar somatosensory stimulation across both conditions). We observed increased rCBF bilaterally in the caudolateral orbitofrontal cortex, in the right anteromedial temporal lobe, and in the right caudomedial orbitofrontal cortex. The elevated recognition thresholds exhibited in patients with resection of the right anteromedial temporal lobe may be accounted for by damage in an area corresponding to that of the rCBF increase. These results suggest that although taste sensation may be computed in the primary taste cortex, recognition requires further processing by structures located in the anteromedial temporal lobe. Furthermore, they point to preferential processing of this higher-order gustatory function by the right cerebral hemisphere.